How Does the Role of Social Support of Parents Affect Students' Learning Motivation? - Hasyim, Sitti Hajerah; Nurjannah, Nurjannah (International Journal of Education, Vocational and Social Science, 2023)
This study aims to determine the role of parental social support in creating learning motivation for students of SMA Negeri 1 Pangkajene, Pangkep Regency. The variables in this study are parental social support (X) and learning motivation (Y). The population includes all students at SMA Negeri 1 Pangkep as many as 308 people with a sample of 46 students in this study. Data collection was carried out in the form of questionnaire statements. The data analysis used in this study is Simple Linear Regression Analysis and t-test to determine the effect of the two variables used. From the results of data analysis, it was concluded that parental social support had a positive and significant effect on the learning motivation of students at SMA Negeri 1 Pangkajene.